Gerenciamento de riscos aplicado aos elementos necessários para a caracterização e execução de obras públicas (projeto básico e executivo) - Flávio Luis Braga Junior (2018)
In construction industry, expenditures on public works in Brazil are quite significant, not only for the high values involved and their representativeness in the budget, as well as for the destination and use by society, demanding a great attention to the theme. Due to the importance of the subject, it is fundamental to know the problems and causes that may hinder the success of all the bidding process and execution of works, especially linked to the elaboration of the projects and promote the management of the risks involved. In this context, this research had as main objective to generate subsidies to the managers and those responsible and involved in the elaboration of the Basic Project to be adopted for the contracting and execution of public works, in order to minimize the need for reformulation or variants during the stages of execution of the works and engineering services. The research, classified as exploratory, used strategies that focused on the delimitation of the problem and objectives, review of the literature, identification of the risks related to the object being studied, involvement of specialists, data analysis obtained using selected tools, with emphasis on the use of probability and impact matrix and diagnosis with consequent planning of responses to the risks. The study was applied face-to-face, through questionnaires and interviews, in a public-law autarchy, which is the executing agency of urban infrastructure works. The results obtained classified 2.86% of the risks as low, 68.57% as moderate and 28.57% as high, which made it possible to visualize the degree of severity of each risk, and to propose ways of acting to manage the risks studied. The research highlighted the importance that should be given to integration and collaboration in project management, the execution of public works and how risk management can contribute to the desired results